Gastrointestinal microphysiological systems. Issue 16 (October 2017) - Blutt, Sarah E; Broughman, James R; Zou, Winnie; Zeng, Xi-Lei; Karandikar, Umesh C; In, Julie; Zachos, Nicholas C; Kovbasnjuk, Olga; Donowitz, Mark; Estes, Mary K
Gastrointestinal diseases are a significant health care and economic burden. Prevention and treatment of these diseases have been limited by the available human biologic models. Microphysiological systems comprise organ-specific human cultures that recapitulate many structural, biological, and functional properties of the organ in smaller scale including aspects of flow, shear stress and chemical gradients. The development of intestinal microphysiological system platforms represents a critical component in improving our understanding, prevention, and treatment of gastrointestinal diseases. This minireview discusses: shortcomings of classical cell culture models of the gastrointestinal tract; human intestinal enteroids as a new model and their advantages compared to cell lines; why intestinal microphysiological systems are needed; potential functional uses of intestinal microphysiological systems in areas of drug development and modeling acute and chronic diseases; and current challenges in the development of intestinal microphysiological systems. Impact statement: The development of a gastrointestinal MPS has the potential to facilitate the understanding of GI physiology. An ultimate goal is the integration of the intestinal MPS with other organ MPS. The development and characterization of nontransformed human intestinal cultures for use in MPS have progressed significantly since the inception of the MPS program in 2012, and these cultures are a key component of advancing MPS. Continued efforts are needed to optimize MPS to comprehensively and accurately recapitulate the complexity of the intestinal epithelium within intestinal tissue. These systems will need to include peristalsis, flow, and oxygen gradients, with incorporation of vascular, immune, and nerve cells. Regional cellular organization of crypt and villus areas will also be necessary to better model complete intestinal structure.